1999
DOI: 10.1902/jop.1999.70.9.1046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Carbon Dioxide Laser on Periodontally Involved Root Surfaces

Abstract: Surface smear layer was present on root surfaces of teeth that were root planed. Laser irradiation of 1 second at 3W completely removed the smear layer with minimal change in the diameter of the dentinal tubules. EDTA and citric acid were also effective in removing smear layer, but the exposed dentinal tubules showed funnel-shaped widening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 19 publications
4
39
0
1
Order By: Relevance
“…Similar results have also been found with CO 2 and Er:YAG laser. [32][33][34][40][41][42][43] In contrast to the favorable effects of laser application found in the above studies, several studies have reported negative effects of the Nd:YAG laser when used directly on root surfaces due to carbonization and melting effects. The Nd:YAG laser application reported by some investigators exhibited, under SEM analysis, surface alterations such as charring, crater formation, and cement meltdown.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Similar results have also been found with CO 2 and Er:YAG laser. [32][33][34][40][41][42][43] In contrast to the favorable effects of laser application found in the above studies, several studies have reported negative effects of the Nd:YAG laser when used directly on root surfaces due to carbonization and melting effects. The Nd:YAG laser application reported by some investigators exhibited, under SEM analysis, surface alterations such as charring, crater formation, and cement meltdown.…”
Section: Discussionmentioning
confidence: 90%
“…In previous clinical studies, it has been demonstrated that lasers are an effective tool in the field of root conditioning to improve the outcome of regenerative periodontal therapies by favoring the attachment of the regenerated periodontal structures. [32][33][34][35][36][37][38][39][40][41][42][43] The Nd:YAG laser has been reported to remove the smear layer, uncovering dentinal tubules and exposing collagen fibers on root surfaces. 37,38 The Nd:YAG laser, with noncontact delivery mode and short irradiation time, has caused no damage to or alteration of root surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When used with relatively low energy output in a pulsed and/or defocused mode, CO 2 l a s e r s h a v e b e e n u s e d t o a c h i e v e root conditioning, detoxification, and bactericidal effects on contaminated root surfaces (Coffelt et al, 1997). However, at low energy outputs in a continuous mode, it is unable to remove subgingival calculus and when used with high energy outputs, especially in a cw mode, it is inappropriate for calculus removal due to major thermal side effects, such as carbonization, melting and cracking on the cementum and dentin (Misra et al, 1999). Nd:YAG laser presents low absorption by water, which produces scattering of its energy and thus a great penetration into the tissues.…”
Section: Lasers On Dental Hard Tissuesmentioning
confidence: 99%
“…Of these, Citric acid, EDTA and Tetracycline hydrochloride have received the most interest. [5] Citric acid has been shown to alter the surface characteristics of treated root surface by removing the smear layer, demineralizing the planed surfaces and eluting bacterial endotoxins from the pathologically altered cementum surfaces. [6], [7], [8] It is also capable to partially expose dentin collagen 9 which is important to increase collagen splicing, improve fibrin linkage, and consequently inhibit epithelial down growth.…”
mentioning
confidence: 99%